2015
DOI: 10.1051/0004-6361/201525644
|View full text |Cite
|
Sign up to set email alerts
|

Dust production 680–850 million years after the Big Bang

Abstract: Dust plays an important role in our understanding of the Universe, but it is not obvious yet how the dust in the distant universe was formed. I derived the dust yields per asymptotic giant branch (AGB) star and per supernova (SN) required to explain dust masses of galaxies at z = 6.3-7.5 (680-850 million years after the Big Bang) for which dust emission has been detected (HFLS3 at z = 6.34, ULAS J1120+0641 at z = 7.085, and A1689-zD1 at z = 7.5), or unsuccessfully searched for. I found very high required yield… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 117 publications
5
92
0
Order By: Relevance
“…The importance of dust growth by accretion for the total dust abundance has already been shown for various galaxy samples by many authors (e.g. Dwek et al 2007;Michałowski et al 2010aMichałowski et al , 2010bHirashita & Kuo 2011;Valiante et al 2011;Kuo & Hirashita 2012;Mancini et al 2015;Michałowski 2015). Recent experiments by Rouillé et al (2014) showed that accretion actually occurs in cold environments.…”
Section: Constraint On the Parametersmentioning
confidence: 83%
“…The importance of dust growth by accretion for the total dust abundance has already been shown for various galaxy samples by many authors (e.g. Dwek et al 2007;Michałowski et al 2010aMichałowski et al , 2010bHirashita & Kuo 2011;Valiante et al 2011;Kuo & Hirashita 2012;Mancini et al 2015;Michałowski 2015). Recent experiments by Rouillé et al (2014) showed that accretion actually occurs in cold environments.…”
Section: Constraint On the Parametersmentioning
confidence: 83%
“…By courtesy of S. Liljegren grated light of galaxies. Estimates suggest that AGB stars are a major source of dust in the Milky Way (e.g., Tielens 2005), but their contribution to dust production in the early universe is still debated (Michałowski 2015, and references therein). To asses the effects of AGB stars on their host galaxies requires, among other things, an understanding of how the mass-loss process depends on stellar metallicity.…”
Section: Stars On the Asymptotic Giant Branch: Evolution And Propertiesmentioning
confidence: 99%
“…Depending on the dust formation mechanism, it is argued that early galaxies have limited dust (e.g. Micha lowski 2015). Indeed, low dust attenuation is often assumed for high-redshift galaxies and is what is expected from the evolution of the colourmagnitude relation (Rogers et al 2014;Bouwens et al 2015).…”
Section: Shape Of the Rest-frame Uv Lf At Z = 8-9mentioning
confidence: 99%